Continuing Medical Education for Primary Care Physicians in Israel: A Cross-Sectional Study. (6th June 2013) - Shvartzman, Pesach; Tandeter, Howard; Vardy, Daniel; Matz, Eran; Heymann, Anthony; Peleg, Roni
Abstract : Acquiring a medical degree is only the beginning of a prolonged learning process. At some point, formal studies end, and continuing medical education (CME) may be left to personal initiative. To assess lifetime learning (LL) and CME among primary care physicians in Israel, a self-administered questionnaire, based on the Jefferson Scale of Physician Lifelong Learning (JSPLL), was mailed to 4, 104 primary care physicians. A total of 979 completed the study, 53.4% males with a mean age of 51.8 ± 8.3 (range 31–79). A logistic regression model showed that male gender (OR = 1.5, P < 0.05 ), teaching (OR = 4.5, P < 0.0001 ), and not working in a rural clinic (OR = 0.6, P < 0.01 ), increased the LL score. The results of the study demonstrate a need to address special subgroups that have a lower tendency to engage in LL activities. Policymakers should develop strategies to increase these physicians' interest in LL activities and the accessibility of these activities to them, including the availability of LL resources at home so physicians can get updates at their convenience. Primary care physicians should also be encouraged to become involved in teaching of any type, as this is a facilitating factor for LL activities.